A structural model of the relationship between product quality, benefits, safety, values and consumer consumption behavior towards herbal products - Mohd Tahir, Ahmad (2022)
Herbal products have been shown to benefit human health and well-being and are now recognized as alternative medicine systems. Despite the growing global demand for herbal products, only a few studies have been conducted to investigate the factors influencing consumers' consumption of herbal products and their consumption patterns in developing countries. Therefore, this research examines the influence of perceived value, perceived product quality, perceived benefits, and product safety on herbal products consumption. This study also examines the mediating effect of perceived value on the relationships between perceived product quality, perceived benefits, product safety, and herbal product consumption. The underpinning theory used in this study was the Stimulus- Organism-Response (SOR) Model. Data were collected using the purposive sampling method among consumers who have experienced consuming herbal products. An online questionnaire was used for this purpose. Data gathered from 252 respondents were analyzed using the partial least squares-structural equation modeling (PLS-SEM) approach. The results revealed that perceived product quality was the most significant factor influencing consumers’ consumption behavior towards herbal products, followed by product safety. However, perceived value did not mediate the relationships between perceived product quality, perceived benefits, product safety, and consumption of herbal products. Marketers should emphasize on quality and safety elements if they want to attract consumers to buy herbal products. Advertisers and herbal product manufacturers should work together to demonstrate the quality and safety of herbal products to the general public. This research has extended the findings on herbal product consumption from a developing country's perspective. In addition, future research directions are furnished